On valence electron density, energy dissipation and plasticity of bulk metallic glasses - Pang, Jianjun (2013)
In conventional crystalline alloys, valence electron density (VED) is one of the most significant factors in determining their phase stability and mechanical properties. Extending the concept to metallic glasses (MGs), it is found, not totally surprisingly, that their mechanical properties are VED-dependent as in crystalline alloys. Interestingly, the whole VED region can be separated into two zones: Zone 1 consists of Mg-, Ca-, and RE-based (RE for rare earth) alloys; Zone 2 consists of the rest of MGs. In either zone, for each type of MGs, Poisson's ratio generally decreases as VED increases. From the energy dissipation viewpoint proposed recently, the amorphous plasticity is closely related to the activation energy for the operation of shear-transformation-zones (STZs). Smaller STZ activation energy suggests higher ductility because STZs with lower activation energy are able to convert deformation work more efficiently into configurational energy rather than heat, which yields mechanical softening and advances the growth of shear bands (SBs). Following this model, it is revealed that the activation energies for STZ operation and crystallization are certainly proportional to VED. Thus, it is understood that, in Zone 2, MGs have a smaller VED and hence lower activation energies which are favorable for ductility and Poisson's ratio. In Zone 1, MGs have the lowest VED but apparent brittleness because either of low glass transition temperature and poor resistance to oxidation or of a large fraction of covalent bonds.